A review of botanical, phytochemical, and pharmacological properties of Alcea rosea L. - Zahra Lorigooini; Zohreh Azadeh; Shirin Asgharian; Solomon Habtemariam; Abdolmajid Taheri (Shahrekord University of Medical Sciences, 2023)
Background and aims: This article was written to better introduce Alcea rosea as a valuable medicinal plant to the medical and pharmaceutical communities and the general public for industrial and traditional uses as a valuable medicinal plant. Methods: The results were gathered from scientific papers and databases to find flavonoids, phenolic acids, amino acids, fatty acids, anthocyanins, polysaccharides, and pharmacological activities in A. rosea. Sixty-two articles were found, and 51 were used for our final results. Results: Studies have shown that flowers, roots, seeds, and other parts of the plant exert antioxidant, antimicrobial, anti-inflammatory, cytotoxic, sedative, analgesic and anti-cough effects due to the presence of valuable phytochemical compounds such as anthocyanins, pectin, starch, monosaccharide, disaccharide, mucilage, flavonoids (hypolaetin-8-glucoside, isoquercitrin, kaempferol, caffeic acid, p-coumaric acid), coumarins, scopolamine, phytosterol, tannins, asparagine, and certain amino acids. Conclusion: Alcea rosea, as a rich source of secondary metabolites, can have diverse applications in medical and food research.